2015
DOI: 10.18393/ejss.07093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bio-fertilizers application on microbial diversity and physiological profiling of microorganisms in arable soil

Abstract: In laboratory assay, the diversity of bacteria and microscopic fungi and the community-level physiological profiling (CLPP) of microorganisms were observed after the addition of bio-sludge (40 t.ha-1) from a biogas station and addition of bio-fertlizers-AZOTER (10 dm-3 .ha-1) to the arable soil with PCR-DGGE and BIOLOG ® method (Eco Plates). The differences were recorded in the microbial diversity (bacteria and microscopic fungi) among variants according to the Shannon index. The differences in community of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…At harvesting, application of chemical fertilizer alone showed lower microbial count for bacterial group compared to inoculated ones. The results corroborate with the finding of Mandic et al (2011) and Javoreková et al (2015) who reported that the application of biofertilizers alone with organic manures resulted in enhanced microbial activity. Nutrient status of soil: At the time of transplanting N level in soil was140 kg ha -1 , P level was 32 kg ha -1 and K level was 150 kg ha -1 .…”
Section: Resultssupporting
confidence: 92%
“…At harvesting, application of chemical fertilizer alone showed lower microbial count for bacterial group compared to inoculated ones. The results corroborate with the finding of Mandic et al (2011) and Javoreková et al (2015) who reported that the application of biofertilizers alone with organic manures resulted in enhanced microbial activity. Nutrient status of soil: At the time of transplanting N level in soil was140 kg ha -1 , P level was 32 kg ha -1 and K level was 150 kg ha -1 .…”
Section: Resultssupporting
confidence: 92%
“…Soil physical data showed an increase in the total moisture content of the samples after treatment with microorganisms, which may be related to aerobic respiration: water and energy produced from substrates and oxygen and carbon dioxide released (Griffin 1996). The pH values found in experimental soil samples (pH 6.5-7.0) were suitable for optimal growth of microorganisms (Fierer et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…However, the addition of microorganisms other than B. cinerea has been found to increase the ability of soil microbial populations to utilize carbohydrates and complex carbon compounds. The method does not distinguish between who does it, added microorganisms or indigenous soil populations stimulated by interspecies interactions (Javorekova et al 2015). .…”
Section: Discussionmentioning
confidence: 99%
“…Biofertilisers amended with inorganic fertiliser are used to increase nutrient availability to plant and can also affect the soil microbial biodiversity (Javoreková et al, 2015). Generally, the microbial consortium includes plant growth promoting rhizobacteria, nitrogen fixing bacteria, plant disease suppressive bacteria and fungi, soil toxicant degrading microbes, actinomycetes which are the increase in the vegetative growth of the OPS was due to the uptake of N from the soil as this nutrient is responsible for chlorophyll content and it is also vital for synthesis of food material in plants (Fraile et al, 2015).…”
Section: Resultsmentioning
confidence: 99%